Understanding the Narrative of Nationalism and Humanism by the Media Wayang Perjuangan in History Learning (Paramita: Historical Studies Journal, 2022)
Teaching history in the era of Industrial Revolution 4.0 requires a transformation in media use. Conventional media such as PowerPoints and visual aid no longer attract students. This study aims to analyze the narrative understanding of students’ nationalism and humanism received through the media wayang perjuangan in history learning. This research was carried out with a descriptive method. This research data is qualitative and quantitative. The data were collected using observation, interview, and test techniques. The data analysis techniques used were qualitative and quantitative analysis. The results of this study are (i) quantum teaching becomes a relevant learning model for the application of media wayang perjuangan; (ii) students’ basic knowledge about the history of the proclamation of Indonesian independence became the minimum capital in receiving the narrative from the media wayang perjuangan; (iii) most of the students accepted wayang perjuangan as an alternative medium, and (iv) students reject the idea of imperialism based on an understanding of nationalism and humanism. These two ideas are the most dominant content and impact when taught using the media wayang perjuangan. In conclusion, the media wayang perjuangan can transmit academic ideas of nationalism and humanism resulting from the dialogue process. Thus, this media can be said to be relevant for teaching history on the material of the independence proclamation. However, this media’s implementation is still needed for other historical material to see the media wayang perjuangan’s relevance further. Pengajaran sejarah di era Revolusi Industri 4.0 membutuhkan transformasi penggunaan media. Media konvensional seperti PowerPoint dan alat bantu visual tidak lagi menarik minat siswa. Penelitian ini bertujuan untuk menganalisis pemahaman naratif tentang nasionalisme dan humanisme siswa yang diterima melalui media wayang perjuangan dalam pembelajaran sejarah. Penelitian ini dilakukan dengan metode deskriptif. Data penelitian ini adalah kualitatif dan kuantitatif. Pengumpulan data dilakukan dengan teknik observasi, wawancara, dan tes. Teknik analisis data yang digunakan adalah analisis kualitatif dan kuantitatif. Hasil penelitian ini adalah (i) quantum teaching menjadi model pembelajaran yang relevan untuk penerapan media wayang perjuangan; (ii) pengetahuan dasar siswa tentang sejarah proklamasi kemerdekaan Indonesia menjadi modal minimal dalam menerima narasi dari media wayang perjuangan; (iii) sebagian besar siswa menerima wayang perjuangan sebagai media alternatif, dan (iv) siswa menolak gagasan imperialisme berdasarkan pemahaman nasionalisme dan humanisme. Kedua gagasan ini merupakan isi dan pengaruh yang paling dominan ketika diajarkan dengan menggunakan media wayang perjuangan. Kesimpulannya, media wayang perjuangan dapat mentransmisikan ide-ide akademik tentang nasionalisme dan humanisme yang dihasilkan dari proses dialog. Dengan demikian media ini dapat dikatakan relevan untuk pembelajaran sejarah pada materi proklamasi kemerdekaan. Namun, implementasi media ini masih diperlukan untuk materi sejarah lainnya untuk melihat lebih jauh relevansi media wayang perjuangan. Cite this article: Utomo, C.B. (2022). Understanding the Narrative of Nationalism and Humanism by the Media Wayang Perjuangan in History Learning. Paramita: Historical Studies Journal, 32(2), 295-305. http://dx.doi.org/10.15294/paramita.v32i2.38578